Two new species of Homalotrichus Solier, 1849 (Coleoptera: Staphylinidae) from Peru - Pérez, Luis; Rodríguez, Maryzender; Asenjo, Angélico (Zootaxa, 2018)
Two new species of Homalotrichus Solier, 1849 are described from the Peruvian highlands: H. yana sp. nov. (Cuzco and Junin) and H. shapra sp. nov. (Cajamarca). Photographs and drawings of the major diagnostic characters are provided for the new species. This contribution confirms the occurrence of the genus in Peru.